Jiuying Cheng: capstone - Cheng, Jiuying, artist (Colorado State University. Libraries, 2018)
The artist's statement: As a graphic designer, I always believe design can help people live better lives because the design provides the visual and convenience benefits. Hence, I think the most important things for design is whether it functions well and whether is helping people in some ways like conveying and understanding information. In my process of design, I always do lots of researches for the audience in order to figure out the best solution. Any material and tools can be used, and they are not limited to the digital works or paper works. For me, everything is full of possibilities and can be applied for my design. Also, because my multiculturalism, I know Chinese, American and Japanese designs and people's different design perspectives from those countries. I am very competitive to be an international graphic designer. For me, design is a never finished work. Everything can always get better, including me as a designer. Hence, I never stop pushing myself to be a better designer technically and emotionally. You should find my work is always in the process of innovation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design